A model of biodiversity taxonomy database (iTaxo) for managing and analysing Kenyir landscape biodiversity data - Salwana, Mohamad; Mustafa, Man; Mohd Tajuddin, Abdullah (IOP Publishing, 2020)
Biodiversity data management and analysis is a complex task that must be handled by biodiversity researchers. The large amount of data and complicated interaction of the data are the main problem in the biodiversity field. Data accessibility also becomes the main issue to create a data sharing environment among other biodiversity researchers. This is important element since the data is related to each other. A standardized form of data model for biodiversity data is not well implemented in real world. This study discussed about the database model for biodiversity taxonomy data (iTaxo) in order to manage the biodiversity data. We implement the Kenyir landscape which is located at the state of Terengganu in Malaysia as our case study data since the landscape is rich with biodiversity species and ecosystem. As a result, the model can be applied to manage, analyse and evaluate the biodiversity status at the landscape for conservation effort.